2021
DOI: 10.1371/journal.pmed.1003546
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of kidney function after dialysis initiation in children and adults in the US: A retrospective study of United States Renal Data System data

Abstract: Background Little is known about factors associated with recovery of kidney function—and return to dialysis independence—or temporal trends in recovery after starting outpatient dialysis in the United States. Understanding the characteristics of individuals who may have the potential to recover kidney function may promote better recognition of such events. The goal of this study was to determine factors associated with recovery of kidney function in children compared with adults starting dialysis in the US. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 24 publications
(13 reference statements)
3
24
0
Order By: Relevance
“…In 2021, Elaine et al showed that peritoneal dialysis is associated with less kidney function recovery both in the adult and children population, from USRDS database. This study also showed that patients aged 18–30, patients received dialysis owing to ATN or AIN, and those with no or low comorbidities are associated higher chances of recovery 5 . The controversial association between modalities and kidney recovery remains despite these large‐scale studies.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In 2021, Elaine et al showed that peritoneal dialysis is associated with less kidney function recovery both in the adult and children population, from USRDS database. This study also showed that patients aged 18–30, patients received dialysis owing to ATN or AIN, and those with no or low comorbidities are associated higher chances of recovery 5 . The controversial association between modalities and kidney recovery remains despite these large‐scale studies.…”
Section: Discussionmentioning
confidence: 55%
“…This study also showed that patients aged 18-30, patients received dialysis owing to ATN or AIN, and those with no or low comorbidities are associated higher chances of recovery. 5 The controversial association between modalities and kidney recovery remains despite these largescale studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sustained recovery of kidney function (RKF) is defined as the persistent discontinuation of kidney replacement treatment (KRT) in patients affected by end-stage kidney disease (ESKD) under maintenance dialysis [ 1 ]. Recent large surveys have reported that the prevalence of RKF is surprisingly high (4.5%) [ 2 , 3 ]. This finding is unexpected because (I) ESKD is an irreversible and permanent loss of renal function and (II) chronic dialysis worsens ischemic renal injury, therefore, hampering RKF [ 2 ].…”
Section: Introductionmentioning
confidence: 99%